Esófago de Barret en Pediatría: Revisión de la literatura a propósito de un caso. - TORI TORI, Carlos; ARIAS STELLA, Javier; TREFOGLI REY, Pablo (Revista Médica Herediana, 2013)
This patient presented at one year of age with a dry and persistent cough prodominantly nocturnal, pneumonia on two occasions, and signs and symptoms compatible with bronchial asthma. Due to the high incidence of gastroesophageal reflux in patients with esophageal atresia, an entity that could be responsible for his symptoms, diagnostic procedures were done to confirm this diagnosis, and treatment was begun with cisapride during one month, but without improvement. It was then that a esophagogastroscopy was performed and Barrett’s esophagus was diagnosed. The patient was medicated with cisapride and omeprazole, and two months later a Thal Fundoplication was done. The patient has continued on cisapride and omeprazole with great improvement, being asymptomatic for a period of nine months, and having had only on one occasion a respiratory crisis due to bronchospasm. A repeat esophagogastroscopy has been planned one year after his operation.